Selection and judicial review system: a study from the jurisprudence of the ecuadorian Constitutional Court - Bravo Rivadeneira, María Sol (2024)
The faculty of selection and review is a legal institution recently included in the 2008 Constitution of the Republic of Ecuador, a provision that empowers the Constitutional Court to issue rulings that establish binding jurisprudence. This paper aims to determine whether the Constitutional Court is competent to rule on the merits of a case selected under the faculty of selection and review. The importance of this issue arises from the fact that this faculty, rather than fulfilling its constitutional purpose of ensuring legal certainty, has been distorted, leading to rights violations by the highest body responsible for protecting them. Using both qualitative and quantitative research methods, including data triangulation and case law analysis, this study was constructed. The results indicate that when the Constitutional Court reviews a case under this faculty, it decides on the merits of the dispute and alters the legal status of the parties involved, thereby affecting their right to legal certainty. The conclusion is that the Constitutional Court of Ecuador, under this faculty, has overstepped its functions, resulting in rights violations.